The political economy of civil society and human rights - Madison, Gary Brent (Routledge studies in social and political thought., 1998)
Madison uses the concept of civil society and his distinctive version of 'communicative rationality' to provide a closely-argued and robust defence of the neo-liberal political and economic tradition. Writing with considerable elegance and humour, the author draws on the hermeneutical and neo-pragmatist traditions, and on a diverse range of evidence and discussion, mainly concerning transitional economies and societies in Eastern Europe and around the world. Providing a systematic analysis of the multi-faceted notion of civil society, this book shows in detail how the three main orders of.